Categorizing women: gender and social media during the 2011 Egyptian Revolution - Barnes, Sydney Winston (AUC Knowledge Fountain, 2013)
From February 2011 to July 2012, formerly suppressed political parties struggled to fill the political void post-Hosni Mubarak. While debates about Egypt's political future circulated, individuals as well as dissident factions employed various interpretations of women and their roles to symbolically represent their varying ideologies. Despite the significance and economic value women produce as citizens, many political actors regularly bracket their concerns as irrelevant to the affairs of the state. As a result, political actors have engaged with new strategic techniques to access the various politicized publics that marginalized subaltern groups. The most publicized approach during this time, involved individual's employment of social media, where political actors could not only escape state media's control over information, but also produce their own level of citizen authority. By ethnographically exploring social networking forums and engaging with Cairene political actors, this research argues that a dialectical relationship exists between social media and politicized publics where actors repurpose, and challenge concepts about women to alter the political atmosphere during the 2011 Egyptian Revolution. Using participant observation, semi-structured interviews, and discourse analysis, this research explores how the analytical category of women was contested in social media and to what extent these classifications were manifested in publics found on- and offline. In order to understand the shifting political spheres during the Egyptian revolution, this ethnographic study engages with the symbolic deployment of women as a category, and the relationship between the production of women and publics. Participants of this research were selected amongst a systematic random sampling framework via Twitter; using prevalent hash tags that engaged with discourses about Egyptian women, the 2011 Egyptian revolution, future governance, and cyber activism. Key events served as a methodological frame to constitute case studies. The events were derived from interviews in which, participants defined what they believed to be moments of significance. This research contributes to the literature regarding the effect new communication technologies have on social structures by investigating the implication that genders has online. This is important because the ways women are marked, categorized, and circulated, consequently contribute to shaping future governance and sociopolitical apparatuses.